Answer:
y = -3x
Step-by-step explanation:
(a) Slope
y = mx + b
Choose points (-3, 9) and (3, -9)
m = (-9 - 9)/(3 – (-3))
m = -18/(3 + 3)
m = -18/6
m = -3
=====
(b) y-intercept
y = mx +b
Choose point (0,0).
0 = 0 + b
b = 0
=====
(c) Equation of line
y = mx + b
y = -3x
Yes, it is an equivalent expression because even though you move two pieces of an equation it will still equal the same thing, unless there are parentheses involved.
Answer:
n= -9
Step-by-step explanation:
-3 ( n+5 ) = 12
-3n - 15 = 12
-3n = 12+15
-3n = 27
n = -27/3
n = -9